A Comparison of Neutral and Immune Genetic Variation in Atlantic Salmon, Salmo Salar L. in Chilean Aquaculture Facilities - Vidal-Soto, R (Public Library of Science, 2014)
Genetic diversity was assessed in samples of cultured Atlantic salmon, Salmo salar L., obtained from facilities in Chile between 2005 and 2010, a period of time during which the infectious pathogens Infectious Salmon Anemia (ISA) virus, Caligus rogercresseyi (sea lice), and Piscirickettsia salmonis (salmon rickettsial syndrome) were common. Two panels of microsatellite markers were utilized: one with microsatellites with no known gene associations (neutral) and one featuring microsatellites linked to putative immune-related genes (immune-related). Allelic richness and gene diversity across samples were significantly greater in neutral loci as compared to immune-related loci. Both diversity measures were homogeneous among samples for immune-related loci and heterogeneous among samples for neutral loci. Immune-related loci were identified as FST outliers in pairwise comparisons of samples at a 10-fold higher frequency than neutral loci. These results indicate that neutral and immune-related portions of the Atlantic salmon genome may have differed in response to the gauntlet of pathogens and that monitoring of specific, well characterized immune-related loci as well as neutral loci in cultured species could be useful when disease control and prevention is a goal. © 2014 Portnoy et al.